2003
DOI: 10.1099/ijs.0.02366-0
|View full text |Cite
|
Sign up to set email alerts
|

Oleispira antarctica gen. nov., sp. nov., a novel hydrocarbonoclastic marine bacterium isolated from Antarctic coastal sea water

Abstract: Oleispira antarctica gen. nov., sp. nov., a novel hydrocarbonoclastic marine bacterium isolated from Antarctic coastal sea water The taxonomic characteristics of two bacterial strains, RB-8 T and RB-9, isolated from hydrocarbondegrading enrichment cultures obtained from Antarctic coastal marine environments (Rod Bay, Ross Sea), were determined. These bacteria were psychrophilic, aerobic and Gram-negative with polar flagella. Growth was not observed in the absence of NaCl, occurred only at concentrations of Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(145 citation statements)
references
References 29 publications
5
134
2
3
Order By: Relevance
“…A psychrophilic strain of this group (Oleispira antarctica) does not take up common carbohydrates and amino acids as sole C sources, and shows a preference for aliphatic hydrocarbons (Yakimov et al, 2003). This metabolic preference could explain the low leucine uptake for this group seen in the autoradiograms.…”
Section: Discussionmentioning
confidence: 91%
“…A psychrophilic strain of this group (Oleispira antarctica) does not take up common carbohydrates and amino acids as sole C sources, and shows a preference for aliphatic hydrocarbons (Yakimov et al, 2003). This metabolic preference could explain the low leucine uptake for this group seen in the autoradiograms.…”
Section: Discussionmentioning
confidence: 91%
“…and Roseobacter spp., when spiked with crude oil, Alcanivorax spp., when spiked with the branched aliphatic hydrocarbon pristine, and Cycloclasticus spp., when spiked with PAHs [34]). A complementary study to analyze the effects of temperature and added nutrients revealed that Alcanivorax only appeared when nutrients were added, and that organisms affiliated to the genus Oleispira (first isolated as a cold-adapted OHCB from crude-oil enrichments of Antarctic seawater [15], bloomed in microcosms maintained at 4°C [59]. Oleispira was also shown to be present in oil-degrading microbial communities in other microcosm studies performed at low temperatures.…”
Section: Marine Ohcb In Oil-degrading Communitiesmentioning
confidence: 97%
“…The three other genera of the OHCB group, despite being represented by numerous members, are monophyletic and represented by the three type species Oleiphilus messinensis [14], Oleispira antarctica [15] and Thalassolituus oleivorans [16].…”
Section: Taxonomy Of Obligate Hydrocarbonoclastic Bacteriamentioning
confidence: 99%
“…[35] Naphthalene, anthracene, phenanthrene, and pyrene Aeram onas punctata TII [14,53] Phenanthrene and Chrysene Vibrio, Pseudoalteromonas, Marinomonas [31] n-Alkanes aromatic hydrocarbon, naphthalene, phenanthrene and anthracene Cycloclasticus oligotrophus [23,73] n-Alkanes, branched alkanes and alkylbenzenes Alcanivorax sp. [22,29,30,48,75] Aliphatic hydrocarbons, alkanoles, and alkanoates Oleiphilusand, Oleispira [28,74] Alkanes…”
Section: The Degradation Rate Of Branched Hydrocarbons Is Significantmentioning
confidence: 99%